2022
DOI: 10.3389/fninf.2022.877139
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CNN-Learned vs. Handcrafted Features for Detection of Parkinson's Disease Dysgraphia in a Multilingual Dataset

Abstract: Parkinson's disease dysgraphia (PDYS), one of the earliest signs of Parkinson's disease (PD), has been researched as a promising biomarker of PD and as the target of a noninvasive and inexpensive approach to monitoring the progress of the disease. However, although several approaches to supportive PDYS diagnosis have been proposed (mainly based on handcrafted features (HF) extracted from online handwriting or the utilization of deep neural networks), it remains unclear which approach provides the highest discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…However, it can be observed that in the published deep learning-based PD detection models, the analysis was conducted offline [19] , [20] , [21] and was only based on the shape of the drawings, while the dynamics were not considered. Handcrafted features of the dynamics of handwriting were proven to outperform the image analysis using deep convolutional neural networks in detecting PD using handwriting data [14] , [15] , [22] .…”
Section: Introductionmentioning
confidence: 99%
“…However, it can be observed that in the published deep learning-based PD detection models, the analysis was conducted offline [19] , [20] , [21] and was only based on the shape of the drawings, while the dynamics were not considered. Handcrafted features of the dynamics of handwriting were proven to outperform the image analysis using deep convolutional neural networks in detecting PD using handwriting data [14] , [15] , [22] .…”
Section: Introductionmentioning
confidence: 99%